The economics of the entrepreneur and the banker historical roots and contributions to the management of innovation. Issue 2 (23rd May 2019) - Boutillier, Sophie
Abstract : Purpose: The purpose of this paper is to study the nature of the relationship between the entrepreneur and the banker, which is central to any analysis of business creation and innovation management. The author's main purpose is to understand how this relationship has been studied by the pioneer economists of the entrepreneur and to highlight their contribution to the understanding of today's reality. Design/methodology/approach: To do so, the author proposes a sketch of an entrepreneur and banker economics based on the study of six economists (Cantillon, Smith, Bentham, Say, Schumpeter and Baumol) known for their works on entrepreneur theory. In their works, they explained how the (often difficult) relationship between the entrepreneur and the banker is built in a context of multi-uncertainty. They define the entrepreneur in different ways (a risk-taker, a prudent man, a projector, etc.), and put forward different behaviors facing uncertainty through social relations. The relationship between the entrepreneur and the banker can be read according to the grid of analysis of strong or weak ties (Granovetter, 1973). Findings: This analysis demonstrates the importance of trust between the two protagonists. This contribution remains fundamental to study the behavior of financers and entrepreneurs today in the context of business eco-systems, clusters, science parks ‒ in other words, the main places of emergence of innovation. Research limitations/implications: This research leads to the proposal of the main basis of an economics of the entrepreneur and the banker; it can be further developed with the addition of other contributions of historical economists. Practical implications: This research shows the importance of thinking about the ways to build trust within the relation between entrepreneurs and their funders (bankers, venture capital, crowdfunding). Social implications: The analysis of social ties (weak or strong) plays a major role in this relation. Originality/value: The originality of the article is to come back to the works of pioneer economists and to show their contributions to the understanding of today's reality.